A meta-analysis of microbial contaminants in selected ready-to-eat foods in Bayelsa State, Nigeria: Public Health implications and risk-reduction strategies - Sylvester Chibueze Izah; Ebitimitula Nicholas Etebu; Tamaraukepreye Catherine Odubo; Ayobami Omozemoje Aigberua; Ikiemoye Iniamagha (Elsevier, 2022)
Food poisoning is a major public health concern. This study employs a systematic review and meta-analysis to summarise and parameterise microbial densities and isolates in ready-to-eat-foods in Bayelsa State, Nigeria. A random effect meta-analysis model is used to compare the microbial density of these foods across the various locations and occurrence rate of the commonly isolated microbes. Whereas meta-analysis results for total heterotrophic bacteria range from 3.65-6.58 Log CFU/g with a p = 0.01 measure of heterogeneity, I2 =61% and overall effect being insignificantly different (p = 0.73), total fungi range from 3.10-4.03 Log CFU/g with a p = 0.92 measure of heterogeneity, I2 =0% and overall effect being significantly different (p = 0.0001). The measure of heterogeneity for the microbial diversity is p = 0.22, I2 =24% and overall effect is insignificant (p = 0.51). 22 microbial genera are isolated and Staphylococcus aureus, Escherichia coli and Aspergillus species depict the highest occurrence rate of 90.48 - 100%, 82.08-88.57% and 57.14- 100% respectively. The availability of these microbial diversities suggests a possible risk of food-borne diseases, hence, the need [i] to enlighten the preparers, vendors and consumers of ready-to-eat foods on the health threats posed by microorganisms found in the foods, [ii] for surveillance of ready-to-eat foods in the study area by appropriate regulatory agencies, and [iii] for vendors to improve on their storage and packaging materials as well as make provision for sources of heat in show glasses in order to retain the freshness of cooked food over prolonged periods.